Detection of heteroplasmy and nuclear mitochondrial pseudogenes in the Japanese spiny lobster Panulirus japonicus - Seinen Chow (Nature Portfolio, 2021)
Abstract Partial mtDNA cytochrome oxidase subunit I (COI) fragments and near entire stretch of 12S rDNA (12S) and control region (Dloop) of the Japanese spiny lobster (Panulirus japonicus) (n = 3) were amplified by PCR and used for direct nucleotide sequencing and for clone library-based nucleotide sequence analysis. Nucleotide sequences of a total of 75 clones in COI, 77 in 12S and 92 in Dloop were determined. Haplotypes of the clones matched with those obtained by direct sequencing were determined to be genuine mtDNA sequence of the individual. Phylogenetic analysis revealed several distinct groups of haplotypes in all three regions. Genuine mtDNA sequences were observed to form a group with their closely related variables, and most of these variables may be due to amplification error but a few to be heteroplasmy. Haplotypes determined as nuclear mitochondrial pseudogenes (NUMTs) formed distinct groups. Nucleotide sequence divergence (K2P distance) between genuine haplotypes and NUMTs were substantial (7.169–23.880% for COI, 1.336–23.434% for 12S, and 7.897–71.862% for Dloop). These values were comparable to or smaller than those between species of the genus Panulirus, indicating that integration of mtDNA into the nuclear genome is a continuous and dynamic process throughout pre- and post-speciation events. Double peaks in electropherograms obtained by direct nucleotide sequencing were attributed to common nucleotides shared by multiple NUMTs. Information on the heteroplasmy and NUMTs would be very important for addressing their impact on direct nucleotide sequencing and for quality control of nucleotide sequences obtained.